O que mudou e o que ficou? Renovação e reprodução das plantas tipo de apartamentos em João Pessoa entre 1980 – 2016 - Carolino, Aline da Silva (2018)
The present work proposed to examine some examples of apartment projects at João Pessoa, built between the 1980s and 2016. The research addresses the impact of the verticalization process, which may allow us, among other things, to view the evolution of apartments as products, from the point of view of the market and the Architecture and Urbanism academic research. It’s mainly goal is to better understand how the conception of space for different family arrangements takes place in order to recognize social values through the characterization of the transformation effect in the plans offered in the projects of apartment buildings. It is understood that what the real estate market is currently offering can be a good sign of how society accepts to live (or liable of reasonable adjustments) in a given time and space. The buildings whose plans were analyzed are located on the axis of Epitácio Pessoa Avenue, which crosses João Pessoa from the east-west direction towards the sea-center (in an inverse manner to the city’s initial occupation which occurred in the center-sea direction) allowing residents, along the way, to identify different phases of the verticalization process in the city. The analysis was based on aspects related to functional space issues (focusing on the needs program offered in each project), its dimensional issues (total areas, of sectors and rooms in the projects studied) and the space configuration. The method adopted through graphs and tables, as well as the application of spatial syntax, sought to find repetition patterns in the plans and their modifications in diachronic perspective. The results obtained indicated that the projects offered by the real estate market present renovations and reproductions of the domestic space characteristics in the apartment plans. The transformations found in the space point to changes in the domestic work relations, such as the absence of the domestic employee in some Family groups, as well as the decrease in the number of family members and the changes in the relations between them. However, the reproduction of spatial patterns, considering the total area offered in each project, disregards the different ways of living of distinct family groups and suggests the need for a revision in the estate production which increases the quality of the living spaces.